Cultivating Excellence: Unraveling the Nexus of Female Leadership, Organizational Culture, and Lecturer Performance Private Universities - Tetet Cahyati; Marliana B Winanti; Dewi Indriani; Umi Narimawati; Denok Sunarsi (Khazanah Sosial, 2023)
This research explores the intricate interplay between female leadership style, organizational culture, work motivation, and lecturer performance in private universities located in Tangerang City, aiming to shed light on their collective impact on education quality. Employing a quantitative survey approach with a sample of 382 lecturers chosen through simple random sampling, data analysis was executed using Partial Least Square (PLS) software version 3.0. The results unveiled a counterintuitive negative influence of female leadership style on lecturer performance, substantiated by a significant t-statistic value of 2.176 (p-value = 0.030 < 0.05). Conversely, organizational culture exhibited a potent positive effect, with a remarkable t-statistic value of 17.823 (p-value = 0), emphasizing its pivotal role in elevating lecturer performance. In conclusion, this study underscores the need for women in leadership to cultivate a supportive organizational culture to mitigate potential detrimental effects on lecturer performance, ultimately enhancing the overall educational quality of private universities in Tangerang City. These findings have broader implications for similar educational contexts and organizational leadership practices, highlighting the importance of fostering inclusive and conducive environments.